2021
DOI: 10.1093/brain/awab088
|View full text |Cite
|
Sign up to set email alerts
|

Myelin and axon pathology in multiple sclerosis assessed by myelin water and multi-shell diffusion imaging

Abstract: Damage to the myelin sheath and the neuroaxonal unit is a cardinal feature of multiple sclerosis; however, a detailed characterization of the interaction between myelin and axon damage in vivo remains challenging. We applied myelin water and multi-shell diffusion imaging to quantify the relative damage to myelin and axons (i) among different lesion types; (ii) in normal-appearing tissue; and (iii) across multiple sclerosis clinical subtypes and healthy controls. We also assessed the relation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 81 publications
11
78
0
2
Order By: Relevance
“…We emailed 14 study investigators to request additional study data or to seek clarification about study methodology, and 7 kindly replied. Not captured by our search were 5 studies that post-dated our literature search [ 20 , 29 32 ]. These were subsequently included in our sensitivity analyses.…”
Section: Resultsmentioning
confidence: 99%
“…We emailed 14 study investigators to request additional study data or to seek clarification about study methodology, and 7 kindly replied. Not captured by our search were 5 studies that post-dated our literature search [ 20 , 29 32 ]. These were subsequently included in our sensitivity analyses.…”
Section: Resultsmentioning
confidence: 99%
“…12 studies remained for the eligibility assessment; 5 studies were excluded based on the reasons shown on the PRISMA diagram ( Figure 1 ). A total of 7 studies investigating the brain microstructure in patients with MS using NODDI were included and met the inclusion/exclusion criteria for this meta-analysis [ 20 , 23 , 24 , 25 , 26 , 27 , 29 ]. A total of 202 patients with MS (mean age of 40.1 years) and 172 healthy controls (mean age of 35.1 years) were included.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 202 patients with MS (mean age of 40.1 years) and 172 healthy controls (mean age of 35.1 years) were included. The mean MS duration of all the studies was 8.3 years; however, two studies did not report disease duration [ 26 , 29 ]. There was no significant difference in the age and sex distribution between MS patients and healthy controls, with the caveat that one study did not provide information relating to the sex of participants [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NDI relates to neuroaxonal density and has been found to be reduced in the MS WM and cortex, especially in the progressive disease (16,17,26). In ex vivo studies, NDI has also been found to correlate with myelin content (16,27).…”
Section: Discussionmentioning
confidence: 98%